1995
DOI: 10.1002/hep.1840220416
|View full text |Cite
|
Sign up to set email alerts
|

Donor selection limits use of living-related liver transplantation

Abstract: The purpose of this investigation was to assess the applicability of living-related liver transplantation in an established regional transplant program by determining the frequency of acceptable living donors from an unselected population of pediatric transplant candidates and identify specific factors limiting application of this technique. During the period May 1992 to May 1994, all children accepted as transplant candidates at the University of California-San Francisco were evaluated for potential living-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
41
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(44 citation statements)
references
References 16 publications
2
41
1
Order By: Relevance
“…Grewal et al 20 (University of Chicago, Chicago, IL) and Yamaoka et al 18 (Kyoto University, Kyoto, Japan) each reported outcomes of 100 living liver transplant donors with very similar findings. Interestingly, their data have been mirrored by smaller studies in North America 22 and Europe. 23,24 The overall incidence of complications ranged from 15% to 20%, with approximately half classified as serious (requiring either a surgical or interventional procedure or increasing hospital stay) and half classified as not serious.…”
Section: Pediatric Living Liver Transplant Donor Outcomesmentioning
confidence: 90%
See 1 more Smart Citation
“…Grewal et al 20 (University of Chicago, Chicago, IL) and Yamaoka et al 18 (Kyoto University, Kyoto, Japan) each reported outcomes of 100 living liver transplant donors with very similar findings. Interestingly, their data have been mirrored by smaller studies in North America 22 and Europe. 23,24 The overall incidence of complications ranged from 15% to 20%, with approximately half classified as serious (requiring either a surgical or interventional procedure or increasing hospital stay) and half classified as not serious.…”
Section: Pediatric Living Liver Transplant Donor Outcomesmentioning
confidence: 90%
“…Marcos et al 16 and Todo 11 each reported no significant donor complications in series of 40 and 27 right-lobe grafts, respectively, whereas Testa et al 13 reported an overall complication rate greater than 50% in the transplantation of 30 right-lobe grafts. In a survey of 30 North American transplant centers that performed 208 adult LDLTs, Renz et al 22 found an overall donor complication rate of 10%. The most common donor complication was postoperative biliary leak (n ϭ 6), typically treated by percutaneous drainage.…”
Section: Adult Living Liver Transplant Donor Outcomesmentioning
confidence: 99%
“…Renz et al 4 published their experience in the evaluation of 38 potential pediatric transplant recipients. Seventy-five potential donors were identified for these 38 potential recipients.…”
Section: Evaluation For Living Donor Liver Transplantationmentioning
confidence: 99%
“…In a similar context, a number of consensus statements from Europe and the United States (8) have recommended the use of an independent living donor advocate (ILDA) for living organ donors, and this has also been reported in various programs and regional protocols (14)(15)(16)(17)(18)(19)(20)(21)). An ILDA is defined as ''a professional who is not involved in the recipient's care, who advocates the welfare of the potential donor, and ensures safe evaluation and protection of the donor's rights,'' (13) but this role is not necessarily consistent and may vary between programs; for example, it may range from the provision of education, policy monitoring, and donor advocacy to active participation in the evaluation (13).…”
Section: Discussionmentioning
confidence: 99%